Effect of Concentration of Antioxidant Quercetin on Semen Quality of Boer Goat during Cold Storage using Andromed Extender - R. N. B. Athalla; C. D. Nugraha; Suyadi (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2023)
Artificial insemination (AI) is a reproductive technology aimed at increasing livestock productivity resulting in animals with superior genetics. Storing semen at cold temperatures can damage sperm quality, one way to improve semen quality is by adding antioxidants such as Quercetin, which has been shown to have a positive effect on sperm quality. The objective of this research is to determine the effect of Quercetin on sperm quality in cold storage using Andromed extender on 5 years old Boer goat using artificial vagina. The method of this research was using Completed Randomized Design (CRD) Factoral two-factors. Variable being tested was motility, viability, abnormality and membrane integrity of spermatozoa. Data was analyze using Analysis of Variance (ANOVA), if there was a significant or significantly differences of treatment then continued by Duncan’s Multiple Range Test (DMRT). Result showed that additional of quercetin and storage time had a significantly differences (P<0.01) effect on motility, viability and membrane integrity and did not have significant (P<0.05) effect on percentage of abnormality. The best result shown that additional of quercetin at 30 μM diluted with Andromed extender for 24-hour cold storage has the best treatment for semen quality.